Domestic Violence and Sexuality What's Love Got to Do with It? - Donovan, Catherine (2015)
This book provides the first detailed discussion of domestic violence and abuse in same sex relationships, offering a unique comparison between this and domestic violence and abuse experienced by heterosexual women and men. It examines how experiences of domestic violence and abuse may be shaped by gender, sexuality and age, including whether and how victims/survivors seek help, and asks, what's love got to do with it? A pioneering methodology, using both quantitative and qualitative research, provides a reliable and valid approach that challenges the heteronormative model in domestic violence research, policy and practice. The authors develops a new framework of analysis - practices of love - to explore empirical data.